LKPD BERBASIS MIND MAPPING: UPAYA MENDUKUNG PENINGKATAN PENALARAN MATEMATIS PADA MATERI EKSPONEN DAN LOGARITMA - Melinia Astri Fitrianingrum; Christina Kartika Sari (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
The lack of teaching materials that support the exponential and logarithmic learning process to improve students' mathematical reasoning abilities causes this ability to be not optimal. The purpose of research and development was to develop student worksheets based on mind mapping that was valid and feasible in supporting the improvement of mathematical reasoning on exponential and logarithmic material. The research used the ADDIE development (Analysis, Design, Development, Implementation, Evaluation). This article describes only the development stage. First, the analysis phase is carried out through curriculum analysis, student characteristics, and material analysis. In contrast, the design phase is carried out with the preparation of product manufacture, the basic framework related to material, and the trial of product instruments. Next, the development stage consists of making LKPD products based on mind mapping, validation of worksheets, practicality tests, and feasibility tests of worksheets. The research subjects in the analysis stage are mathematics teachers and students, while the researcher is in the design stage. In contrast, the development stage is three experts as validators, user teachers as practitioners, and six students of SMA Negeri 1 Kembang class X in the 2021/2022 academic year. The research data were obtained through observation, documentation, interviews, and questionnaires. The study results indicate that the mind mapping-based LKPD development design has a good category. After being declared valid, the practicality test was carried out on the user teacher and claimed practical with an average score of 4.00. After being declared applicable, the feasibility test was carried out to students by distributing questionnaires and was declared very suitable for use with an average score of 4.05.